Skin ulcerative lesion induced by Acremonium species - Antonio Mastroianni; Valeria Vangeli; Maria Vittoria Mauro; Francesca Greco; Roberto Manfredi; Sonia Greco (Termedia Publishing House, 2023)
Acremonium (Cephalosporium) species are environmentally widespread saprophytes and considered ubiquitous fungal organisms found in soil and air, but in recent years they have been described increasingly as opportunistic microorganisms in immunocompetent patients that have sustained skin injuries. In recent years, the incidence of invasive infections caused by Acremonium species (spp.) has increased probably as a result of more aggressive modern medical modalities such as chemotherapy, transplantation, intravascular central line insertion, prosthetic valves, and dialysis access grafts and more frequent and widespread use of immunosuppressive agents. An intriguing report of a large cutaneous ulcerative lesion by Acremonium spp . is discussed on the ground of the existing literature in this field. The literature search showed only three cases of ulcerative lesions of the skin due to Acremonium spp. infection. There are no standard therapy guidelines for the treatment of these infections, so we aim to summarize and discuss the currently available data on the promising results obtained with voriconazole for the treatment of these ulcerative skin infections. Clinical experience with other drugs, such as VRC is very encouraging.